Rissoidae gastropods of the outer continental shelf and slope off Galicia (NW Spain) - Oliver, Joan Daniel; Gofas, Serge; Urgorri, Victoriano; Díaz-Agras, Guillermo; Templado, José (Zootaxa, 2022)
More than 5000 shells (more than half of them with soft tissues) belonging to the caenogastropod family Rissoidae have been found in samples from several expeditions carried out in the outer continental shelf and slope off Galicia (Northwest Spain) in the depth range 100–2700 m. They belong to 9 genera and 23 species, two of them described as new for science: Alvania candasae sp. nov. and Alvania xelae sp. nov. The most abundant species in the samples were Obtusella macilenta (Monterosato, 1880) and Alvania testae (Aradas & Maggiore, 1844), followed by Alvania cimicoides (Forbes, 1844), Alvania jeffreysi (Waller, 1864) and Gofasia thalassae (Bouchet & Warén, 1993) comb. nov., which is proposed to be assigned to the genus Gofasia instead of Frigidoalvania. Five of the species are typically from upper shelf of which only few empty shells were found (Alvania cancellata, Crisilla semistriata, Manzonia crassa, Onoba semicostata) and their presence in the samples studied was considered accidental. Taxonomic complexity involving the species Alvania electa (Monterosato, 1874), Pseudosetia amydralox Bouchet & Warén, 1993 and Pusillina inconspicua (Alder, 1844) are highlighted.